Game theoretical problems in mechanics - Petrosjan, L. A.; Mursov, N. V. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Л. А. Петросян, Н. В. Мурзов. Теоретико-игровые задачи механикиL. Petrosianas, N. Murzovas. Lošimų teorijos uždaviniai mechanikoje